The impacts of CO2 on sandstone reservoirs in different fluid environments: insights from mantle-derived CO2 gas reservoirs in Dongying Sag, Bohai Bay Basin, China - Wang, Maoyun; Zeng, Jianhui; Li, Chuanming; Qiao, Juncheng; Wei, Wenfei; Zhang, Huanle; Cui, Huwang (Frontiers in Earth Science, 2024)
IntroductionMantle-derived CO2, as an important component of hydrothermal fluids, is widely distributed in petroliferous basins. While previous experimental studies have suggested that CO2 can improve sandstone reservoir quality through mineral dissolution in open fluid setting, they have overlooked its nagetive effects to sandstone reservoir quality by carbonate cementation. Additionally, the roles of various fluid environments in CO2-reservoir interactions have not been studied in detail.MethodsTo systematically investigate the influences of CO2 on sandstone reservoirs, we examine a typical mantle-derived CO2 gas reservoir, Bohai Bay Basin, China. This study employs integrated methods, including electron microscopy, scanning electron microscopy, X-ray diffraction, stable C- and O-isotope analysis, and physical property data. The aim is to investigate the evidence and mechanisms by which mantle-derived CO2 impacts sandstone reservoirs, particularly focusing on its effects in open and closed fluid environments.Results and DiscussionOur findings reveal that dawsonite and ankerite are prevalent within the mantle-derived CO2 gas reservoir, while isotopic analysis of carbonate cements indicates values (δ13C: −9.0‰ to −1.6‰; δ18O: −21.7‰ to −12.7‰) consistent with mantle-derived CO2 and hydrothermal fluids. These pieces of evidence indicate that CO2-rich hydrothermal fluids participate in water-rock interactions, thereby significantly influencing the diagenesis of reservoirs. Further, we notice that CO2 reservoirs adjacent to faults exhibit an open fluid environment, characterized by superior porosity and permeability, more quartz, but fewer feldspar, carbonate, and clay minerals compared to those in closed fluid environments. Notably, kaolinite predominates in open fluid environments, while illite/smectite (I/S) is more common in closed settings. The dual roles of mantle-derived CO2 are highlighted in our analysis: while it enhances reservoir storage and permeability through mineral dissolution, the carbonate cement generated by CO2-water-rock interaction can also adversely affect reservoir quality. In open fluid environments, CO2 facilitates the dissolution of feldspar and carbonate minerals, promoting the timely removal of dissolution by-products (clay mineral) and inhibiting carbonate cementation, thereby improving reservoir properties. Conversely, in closed fluid environments, decreasing CO2 concentrations with depth leads to diminishing dissolution effects and increased carbonate cementation, resulting in reduced reservoir porosity and permeability. Overall, the significance of this study is to correct the deviation in the impacts of CO2 on sandstone reservoirs at laboratory setting through case study of typical mantle-source CO2 gas reservoir.This work can be applied to the studies of reservoir homogeneity and sweet spots in regions with hydrothermal and mantle-derived CO2 activities. However, due to the limitation of CO2 content range (about 15%–70%) in the study case, we are unable to investigate the effects of low-concentration CO2 on sandstone reservoirs, which may affect the generalizability of this work. Besides, the formation temperature and pressure, and salinity of formation water, should be considered when dealing with other cases.